Computational minimization of over-deposition at corners of trajectories in Laser Metal Deposition. (August 2021) - Montoya-Zapata, Diego; Creus, Carles; Moreno, Aitor; Ortiz, Igor; Alvarez, Piera; Ruiz-Salguero, Oscar; Posada, Jorge
Abstract: Avoidance of over-deposition at trajectory corners is relevant in Laser Metal Deposition (LMD) for Additive Manufacturing. Currently available LMD hardware only allows constant material feed (g/s). Therefore, gliding speed of the material dispenser is the remaining tuning variable for controlling metal over-deposition at corners. Existing literature reports trial–error physical experiments, addressing only particular corner angles. In response, this manuscript reports the implementation of a voxel-based simulator of the bead geometry, taking into consideration bead profile, dispenser velocity, material feed, and bead curve geometry. We use it to evaluate two constant-feed tailored-velocity strategies for minimizing material over-deposition at corners.